Porosity Characterization of Carbon Fiber/Epoxy Composite Using Hg Porosimetry and Other Techniques - Monticeli, Francisco Maciel [UNESP]; Montoro, Sergio Roberto; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP] (My University, 2020)
In polymer composites, the porosity acts mainly as a stress concentrator, which has detrimental effects depending on the shape and position of the voids. Also, the presence of voids is detrimental to the mechanical properties, which results in the need for an accurate method for their characterization in terms of morphology, position, and volume fraction. The aim of this study was to establish an appropriate procedure for the measurement of voids in a polymer composite using the mercury porosimetry technique. Data were also collected using the Taguchi approach. Subsequently, the feasibility of applying the Hg porosimetry methodology was confirmed through a comparison with standard techniques. Statistical analysis was used to determine the best Hg porosimetry parameters and pressures between 203 and 231 MPa was found to generate reliable results for the maximum porosity measurement, with no dependence on other parameters. Since the Hg porosimetry, acid digestion, and optical microscopy methods provided porosity results with a statistically significant similarity, it can be concluded that all these methods are feasible for the analysis of voids. Finally, potential benefits of the proposed porosity analysis methodology were highlighted through the characterization of the void volume, position, and morphology. POLYM. ENG. SCI., 60:841–849, 2020. © 2020 Society of Plastics Engineers.